Pemberdayaan ekonomi masyarakat Dusun Kampung Ulau Desa Tanjung Belit melalui peningkatan kualitas produksi gula Aren menuju kemandirian secara ekonomi, pertanian dan hukum di Kabupaten Rokan Hulu - Hayatul Ismi; Shanti Fitriani; Ihda Hasbiyati; Maimunah Maimunah; Ulfia Hasanah; Rismadefi Woferst; Fenny Trisnawati (Unri Conference Series: Community Engagement, 2020)
As we know, the life of the people of Tanjung Pauh Hamlet, Tanjung Belit Village, Rokan Hulu Regency is still fairly traditional. The problem discussed in this research is concerned with the sugar palm farmers in Tanjung Pauh hamlet. The palm sugar produced is very popular with consumers because of its pure taste without a mixture of preservatives or chemicals, and because the manufacturing process prioritizes quality. It's just that due to a shortage of sap water, the production of palm sugar in Tanjung Pauh hamlet can be said to be very little to meet the needs of the community itself. Therefore, we tried to do research by conducting a survey of the location of the palm trees, the location of the palm sugar making, and collecting data on the needs of the palm farmers in Tanjung Pauh hamlet. This study aims to provide guidance to the community of Tanjung Pauh hamlet as a hamlet that has the potential to develop income through improving the quality and marketing of palm sugar. We gave a little idea to the palm farmers in Tanjung Pauh hamlet to produce palm sugar, which is palm sugar which is usually in the form of blocks, which is now being innovated into the form of ant sugar, in order to attract consumers' attention to love palm sugar in Tanjung Pauh hamlet.